Naming practices and cultural meanings of supernatural beings in Banjarese society: An onomastic and linguistic anthropology study - Athiya, Husnul (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
The existence of supernatural beings in Banjarese society reflects culturally constructed understandings transmitted through language, particularly through the names assigned to such entities. This study examines the naming patterns of supernatural beings in Banjarese culture using a linguistic anthropology approach and an inductive analytical method. Data were drawn from eight lexicons collected through non-participant observation and interviews with native speakers. Each lexicon was analyzed using Husen’s (1999) deictic framework and further validated through informant responses and supporting textual sources. The findings show that the naming of Banjarese supernatural beings is systematically organized around two deictic dimensions—personal and spatial—which manifest in three naming patterns: animal-based, human-like, and origin-based. These patterns reveal that naming practices function as cultural representations that encode ecological experience, moral values, and local cosmology. Overall, the study demonstrates that linguistic forms provide a window into the cultural worldview of the Banjarese community and contribute to broader discussions on how language reflects and structures cultural perceptions of the unseen.